The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1021/jm980431g
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Immunosuppressive Activity Relationships of New Analogues of 15-Deoxyspergualin. 1. Structural Modifications of the Hydroxyglycine Moiety

Abstract: A series of new analogues of 15-deoxyspergualin (DSG), an immunosuppressive agent currently commercialized in Japan, was synthesized and tested in a graft-versus-host disease (GVHD) model in mice. Using the general concept of bioisosteric replacement, variations of the hydroxyglycine central "C" region were made in order to determine its optimum structure in terms of in vivo immunosuppressive activity. By this way, the malonic derivative 13a was discovered as the first example of a new series of potent immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…An analysis of the resulting structure-activity relationship (SAR) suggested that the guanidylated alkyl group and hydroxyl amide core were necessary for bioactivity, confirming earlier findings [187,203]. In 1999, Renaut and co-workers increased the stability of the core hydroxyl amide against hydrolysis through the substitution of the hemiaminal group with a carbamate [201]. The resulting product, known as tresperimus (Fig.…”
Section: Spergualin: R = Oh (S)supporting
confidence: 65%
See 1 more Smart Citation
“…An analysis of the resulting structure-activity relationship (SAR) suggested that the guanidylated alkyl group and hydroxyl amide core were necessary for bioactivity, confirming earlier findings [187,203]. In 1999, Renaut and co-workers increased the stability of the core hydroxyl amide against hydrolysis through the substitution of the hemiaminal group with a carbamate [201]. The resulting product, known as tresperimus (Fig.…”
Section: Spergualin: R = Oh (S)supporting
confidence: 65%
“…Factors limiting the utility of 15-DSG are the inherent instability of the molecule at varying pHs in vitro and its rapid metabolic degradation in vivo; 15-DSG also exhibits low oral bioavailability (<5%) [198,201]. Like the parent compound, spergualin, 15-DSG undergoes facile hydrolysis of the hydroxyamide moiety, with a half-life of 48 h at pH 7 and only 2 h at pH 10 (Scheme 1) [201].…”
Section: Spergualin: R = Oh (S)mentioning
confidence: 99%
“…6 Several analogs were obtained recently through organic synthesis. 7,8 One of these compounds, designated LF 15-0195, has demonstrated its efficacy in preventing graft-versus-host disease 8 and in treating collagen type II-induced arthritis 9,10 in mice models. Although LF 15-0195 is now tested in human clinics, the molecular mechanisms of its immunosuppressive activity differ from currently used immunosuppressive agents but remain poorly understood.…”
mentioning
confidence: 99%
“…Subsequent work showed that this molecule has anticancer and immunosuppressive activities [112][113][114]. Synthetic efforts have removed some of the metabolic liabilities of spergualin, including the hydroxyl at carbon 15, which have greatly improved the physical properties of the chemical series [115,116]. The most advanced of the spergualin analogs, 15-deoxyspergualin (15-DSG), is clinically approved in Japan for the treatment of acute allograft rejection, making this molecule the lone Hsp70 inhibitor approved for human use [117,118].…”
Section: Spergualinmentioning
confidence: 99%